Evaluation on PWD 75, standard form of general conditions of contract in Sarawak - Sia, Pik Soon (Universiti Malaysia Sarawak, UNIMAS, 2008)
The General Conditions of Contract, Public Works Department 75 (PWD75) is the most commonly used standard form of condition of contract in the public sector construction projects in Sarawak. PWD 75 currently in use was last revised in May 1961 and there had not been another revision since then. It is very seldom for a set of conditions of contract used in the construction industry to have not been revised for such a long period. Making comparison with some other more recent standard forms of conditions of contract is an effective way to find out any possible miss-out, incompleteness and even inefficiency or unfairness in PWD 75. By this way, some recommendations for improvement of PWD 75 could be made in order to meet the needs of construction industry in nowadays. It is paramount to promote a fair and just construction contract for the entire public sector construction industry in Sarawak so that the local construction industry will grow in a healthy and balance manner.The General Conditions of Contract, Public Works Department 75 (PWD75) is the most commonly used standard form of condition of contract in the public sector construction projects in Sarawak. PWD 75 currently in use was last revised in May 1961 and there had not been another revision since then. It is very seldom for a set of conditions of contract used in the construction industry to have not been revised for such a long period. Making comparison with some other more recent standard forms of conditions of contract is an effective way to find out any possible miss-out, incompleteness and even inefficiency or unfairness in PWD 75. By this way, some recommendations for improvement of PWD 75 could be made in order to meet the needs of construction industry in nowadays. It is paramount to promote a fair and just construction contract for the entire public sector construction industry in Sarawak so that the local construction industry will grow in a healthy and balance manner.